Respostas

2014-01-30T14:36:44-02:00
√3x - y + 2 = 0 
√3x - 3y + 6 = 0 

só usar a formula:

|ax+by+c|/√(a²+b²) = ±|a'x+b'y+c'|/√((a')²+(b')²) 

percebeu o +-? como a questão quer saber o menor, usaremos o -.

|√3x - y + 2| / √√3² + (-1)² = - |√3x - 3y + 6| / √√3²+(-3)²
|√3x - y + 2| / 2 = -|√3x - 3y + 6| / √12
|√3x - y + 2| / 2 = - |√3x - 3y + 6| / 2√3
√3 . |√3x - y + 2| = - |√3x - 3y + 6| 
3x - √3y + 2√3 = -√3x +3y - 6
3x-√3y + 2√3 + √3x - 3y + 6 = 0
3x+√3x - √3y-3y + 2√3 + 6 = 0
(3+√3)x - (√3+3)y + (√3+3)2 = 0
(3+√3)x + (√3+3)2  = (√3+3)y 

só dividir tudo por ((√3+3))) = 

x + 2 = y
1 1 1